The Power Unit Coordinated Control via Uniform Differential Evolution - Zain Abdalla Zahran; Rui Feng Shi; Xiang Jie Liu (Institute of Advanced Engineering and Science, 2013)
This paper modified the differential evolution (DE) algorithm adaptively to solve the power unit coordinated control (PUCC) problem.It was modified in two aspects: 1) a uniform initialization, which was controlled and regulated by a zone factor (m), 2) a regular mutation process, to develop an effective searching process and improve the convergence of the basic DE algorithm. A numerical case study was employed to verify the performance of our proposed uniform differential evolution (UDE) algorithm, by contrast to the performance with the basic DE, genetic algorithm (GA), and particle swarm optimization (PSO) algorithms. The experimental simulation results show that our proposed UDE algorithm has outperformed the other comparative algorithms, which demonstrate the effectiveness and efficiency of the new algorithm.DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2281